Causes of persistent productivity differences in the West German states in the period from 1950 to 1990 - Nicole Waidlein (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2011)
Since the Second World War the West German states show persistent differences in their standard of living. The explanation of the incomplete catching-up process within West Germany is of crucial interest. After identifying productivity as the major growth driving force, this paper investigates the main causes of productivity growth on the state level between 1950 and 1990. With the help of growth theories different determinants of productivity growth are identified. These are innovations, secondary and tertiary human capital, structural change, openness and institutions. Finally, the empirical analysis reveals that three of those determinants are able to explain the persistent differences in the regional productivity levels: innovations, tertiary human capital and structural change.
urn:nbn:de:bsz:100-opus-6219
Keywords: 330; Produktivität; Regionales Wachstum; Teilstaat; Regionale Disparität; Regionale Entwicklung; Alte Bundesländer; Deutschland